Wissenschaft ohne (disziplinäre) Grenzen: Wie sich Interdisziplinarität im deutschen Wissenschaftssystem verankern lässt - Anna Froese (Forschung: Politik - Strategie - Management, 2020)
– Interdisciplinarity has gained significant popularity over the last years as it has the potential for solving complex problems and generating highly innovative research. Yet, the German research system is still structured based on the idea of separated disciplines. This article describes the advantages and challenges of interdisciplinary research. It presents strategies that help fostering interdisciplinary research and implement it as a principle of complementarity.
Keywords: 300